2018
DOI: 10.3151/jact.16.46
|View full text |Cite
|
Sign up to set email alerts
|

Computational Life Assessment of ASR-damaged RC Decks by Site-Inspection Data Assimilation

Abstract: To estimate the remaining life of existing RC bridge decks damaged by alkali silica reaction (ASR), multi-scale numerical analysis with chemo-hygral model is integrated with visual inspection data at site. First, the applicability of the poro-mechanical models for ASR expansion in the multi-scale frame are examined with the experiments of the real scale RC slabs and the model is validated to bring about fair prediction of the 3D anisotropic expansion and the fatigue life of the slabs. Second, visually inspecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Then, the ASR has multiple functions as both self-breaking of concrete and self-curing agents. Figure 18 shows the experiment of RC slab with ASR-induced damage under high cycle fatigue loads [36]. It is found that the life of ASR damaged slabs is prolonged compared to the reference with no initial cracking.…”
Section: Asr and Fatiguementioning
confidence: 99%
“…Then, the ASR has multiple functions as both self-breaking of concrete and self-curing agents. Figure 18 shows the experiment of RC slab with ASR-induced damage under high cycle fatigue loads [36]. It is found that the life of ASR damaged slabs is prolonged compared to the reference with no initial cracking.…”
Section: Asr and Fatiguementioning
confidence: 99%
“…The silica gel generation, migration and the scale-dependent expansion could be simulated by the ASR model. The model has been verified by experiments and used to predict the fatigue life of ASR damaged RC decks (Takahashi et al 2018).…”
Section: Introductionmentioning
confidence: 98%
“…An alkali-aggregate reaction (AAR) is a pathology of degraded concrete. It is a common issue in the concrete structures of nuclear facilities as well as in general civil infrastructure (Hayes et al 2018;Kawabata et al 2018aKawabata et al , 2018bTakahashi et al 2018;Pourbehi and van Zijl 2019;Li et al 2020). In Japan, the reinforced-concrete (RC) turbine generator foundation of the Ikata nuclear power plant (NPP) Unit 1 of Shikoku Electric Power exhibits expansion as a result of AAR, as reported by Manabe et al (2016).…”
Section: Introductionmentioning
confidence: 99%